The Effect Of Soaking In Warm Water With Aromatic Ginger For Edema In Pregnant Mothers - Titin Novayanti Dey; Basyariah Lubis; Siti Sarah Bintang (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
During pregnancy, there are changes in pregnant women both physically and psychologically that often make pregnant women feel uncomfortable. Swelling in the legs is one of the pregnancy discomforts that pregnant women often complain about and 80% is found in third trimester pregnant women. The purpose of this study was to determine the effect of foot soaking using warm water mixed with kencur on edema in pregnant women. The research method uses a Quasi Experiment with One Group Pretest-Posttest Design without a control group. The research site was at Karang Anyar Health Center in 2022, the research was carried out in May - June. The population was 57 pregnant women, the sampling technique used purposive sampling where the samples were taken in accordance with predetermined inclusion criteria. The sample in this study amounted to 12 third trimester pregnant women who were given an intervention in the form of foot soaking using warm water mixed with kencur for 5 consecutive days. The data obtained are based on primary and secondary data. Data analysis is the Paired Sample T-Test. The results showed that there was a decrease in the level of pitting edema from pre-intervention to post-intervention, namely a decrease from grade II to grade I as many as 8 people (66.6%) with p <0.05 (p = 0.003). The conclusion is that there is an effect of soaking the feet using warm water mixed with kencur on leg edema in pregnant women.